2001
DOI: 10.1017/s1355838201002576
|View full text |Cite
|
Sign up to set email alerts
|

Specific metal-ion binding sites in a model of the P4-P6 triple-helical domain of a group I intron

Abstract: Divalent metal ions play a crucial role in RNA structure and catalysis. Phosphorothioate substitution and manganese rescue experiments can reveal phosphate oxygens interacting specifically with magnesium ions essential for structure and/or activity. In this study, phosphorothioate interference experiments in combination with structural sensitive circular dichroism spectroscopy have been used to probe molecular interactions underlying an important RNA structural motif. We have studied a synthetic model of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…Concentrations of Cd 2+ above 1 mM inhibit the ribozyme reaction with a steep concentration dependence (see, e.g., Figures S4 and S5A). The small Cd 2+ stimulation observed for the U258 variant ribozymes is consistent with coordination of a metal ion important for structural stability, as proposed by Lindqvist et al [78]. …”
Section: Resultssupporting
confidence: 86%
“…Concentrations of Cd 2+ above 1 mM inhibit the ribozyme reaction with a steep concentration dependence (see, e.g., Figures S4 and S5A). The small Cd 2+ stimulation observed for the U258 variant ribozymes is consistent with coordination of a metal ion important for structural stability, as proposed by Lindqvist et al [78]. …”
Section: Resultssupporting
confidence: 86%
“…Hydroxide formation within the coordination sphere of Mg 2+ is also believed to reduce the coordination number . Related issues regarding the use of Mn 2+ in rescue experiments have recently been indicated in different contexts. ,,, …”
Section: 45 Water−hydroxide Equilibria and The “Metal-ion Switch Expe...mentioning
confidence: 99%
“…The structure and function of DNA and RNA strongly depend on their interactions with divalent cations. These cations are found to interact with different sites at the surface of nucleic acids: phosphate oxygens, sugar oxygens and nucleotides. Besides the fact that the presence of magnesium ions in solution leads to a decrease in the persistence length of DNA and increases the melting temperature of DNA double-helices, , magnesium is also involved in the site-specific hydrolysis of the polyester bond of DNA, both enzymatically and in protein-free systems, , and in RNA. , It has also been reported that divalent metal cations stimulate the formation of DNA and RNA triple helices , and stabilize other noncanonical structures such as quadruple helices …”
Section: Introductionmentioning
confidence: 99%
“…Besides the fact that the presence of magnesium ions in solution leads to a decrease in the persistence length of DNA 5 and increases the melting temperature of DNA double-helices, 6,7 magnesium is also involved in the site-specific hydrolysis of the polyester bond of DNA, both enzymatically [8][9][10] and in protein-free systems, 11,12 and in RNA. 13,14 It has also been reported that divalent metal cations stimulate the formation of DNA and RNA triple helices 15,16 and stabilize other noncanonical structures such as quadruple helices. 17 To understand the nature of the interaction between nucleic acids and metal cations, a number of computational investigations have recently been made.…”
Section: Introductionmentioning
confidence: 99%